Adaptation of Teacher Power Use Scale to Lower Secondary Students and Student Teachers - Kateřina Vlčková; Jan Mareš; Stanislav Ježek (Czech Pedagogical Society, 2016)
Power can be defined as an ability to influence opinions, values, and behaviour of others. The realisation of curricular aims is enabled by clearly established power relationships in classes. Newly qualified teachers often struggle with establishing power relationships. French and Raven's influential typology of social power as a relational phenomenon distinguishes coercive, reward, legitimate, referent, and expert bases of teacher power. In our methodological study we adapted Teacher Power Use Scale - TPUS (Schrodt, Witt, & Turman, 2007) that measures these power bases. The adaptation focuses (instead of tertiary teachers, their students, and Anglo-Saxon context) on student teachers, lower secondary students, and reflects the Czech sociocultural context. The non-probability adaptation sample consists of 1686 students from 96 lower secondary classes taught by 96 student teachers during their long term teaching practice. Our data basically support French and Raven's theory and the original TPUS, except that the structure of student teacher power bases seems to be naturally simpler in the perception of lower secondary students. Above all, legitimate and coercive student teachers power bases were strongly inter-correlated, i.e. perceived by students as one factor; similar to teacher power bases structure in other Czech data